Necesidad de reformar el artículo 42 del codigo del trabajo numeral 33, inciso 1,3,4,5,6 propuesta de reforma. - León Ullaguari, Julio César (2017)
The current Constitution of the Republic of the Ecuador of the year 2008, guarantee in their Art. 47, 5 numeral establish that it is a fundamental right for people with disability to consent to the work under conditions of equality of opportunities, through political public that allow their labor inclusion so much in the private sector as public. From the environment of action of the legislation they are important normative bodies, just as the Law about Disabilities that establishes a series of access prerogatives mainly to basic services of high-priority attention to people with disability, as well as excuses tributary and other prerogatives that aid the rights of these people. In the concretely labor environment the Code of the Work settles down in its Art. 42 the obligations and the employers' duties, and in their numeral one 33 establish an obligatory percentage for the recruiting of people with disability on the part of the employers, but the current legal regulation more than to achieve their essential purpose, it has brought serious inconveniences so much juridical as economic and social. The pecuniary sanction settled down in the Art. 42 numeral 33 of the Code of the Work, it prescribes that the employer that doesn't fulfill the minimum percentage of hard-working with disability will be sanctioned with an equivalent ticket to ten monthly remunerations from the validity of the Law Reformatory Number 28-2006 published in the R. O. Number 198 of January 30 the 2006. That which harms the principle of proportionality, because the ticket is increased extensity, because just as it is edited the Regional Directions of Work they have proceeded to impose tickets that are increased by every month until the imposition of the ticket, creating exaggerated sums to pay that they skirt the thirty thousand dollars. Another problem is that the nonfulfillment is based on the percentage, and when this percentage doesn't give whole numbers as a result, that is to say that the percentage application gives 3,5 workers for example with disability, like it is logical nobody can hire half of a person, but the nonfulfillment of that fractional part already consists as infraction to the disposition of the Code of the Work, and in the whole country the negative effects of the imposition of too strong tickets have already been evidenced that can put in economic risk to the company deprived in the Ecuador. The obligation of hiring people with disability is for the public and private environment, but the sanction settles down with inequality, because in the public sector it is fined with an unified basic salary a single time, while to the private company it sanctions it to him with ten basic remunerations unified in monthly form. Therefore the Art. 42 numeral 33 of the Code of the Work require an urgent legal reformation that proporcionalice the ticket in order to that although it is necessary to guarantee the inclusion of people with disability, it is also certain that the legal norms should not produce unnecessary economic damages.